Learning and Retention Using Virtual Reality in a Decontamination Simulation. Issue 4 (July 2016) - Smith, Sherrill J.; Farra, Sharon; Ulrich, Deborah L.; Hodgson, Eric; Nicely, Stephanie; Matcham, William
Abstract: AIM: The purpose of this study was to examine the longitudinal effects of virtual reality simulation (VRS) on learning outcomes and retention. BACKGROUND: Disaster preparation for health care professionals is seriously inadequate. VRS offers an opportunity to practice within a realistic and safe environment, but little is known about learning and retention using this pedagogy. METHOD: A quasiexperimental design was used to examine the use of VRS with baccalaureate nursing students in two different nursing programs in terms of the skill of decontamination. RESULTS: Results indicate that VRS is at least as good as traditional methods and is superior in some cases for retention of knowledge and performance of skills. CONCLUSION: VRS may provide a valuable option for promoting skill development and retention. More research is needed to determine how to prepare nurses for skills that may not be required until months or even years after initial introduction.